2021
DOI: 10.1111/iej.13592
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated MTA Repair HP reduced biofilm and can cause reparative action at a distance

Abstract: Aim To evaluate in vitro whether MTA Repair HP can induce repair processes at a distance, including its effects on biofilm, cell viability, migration, production of TGF‐β, phosphate and ALP, evaluated through MTA diluted extracts. Methodology Initially, antibacterial tests were performed with the bacterium Streptococcus mutans (ATCC 25175) in the presence of MTA extracts (dilutions of 1:1, 1:2 and 1:4). Growth inhibition assay by microdilution in broth, antibiofilm plate assay of young biofilm and antibiofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our findings demonstrated that although HDPs, MTA or a combination of both did not cause inhibition of S. mutans growth under planktonic conditions, these materials have the potential of reducing biofilm performed in 24 h and biofilm performed over 7 days biofilms of S. mutans . Our group also recently demonstrated the ability of MTA extracts to reduce biofilm performed in 24 h and S. mutans biofilm performed over 7 days 32 . Besides, previous studies have demonstrated that the antibiofilm capability of IDR1018 is directly related to its concentration 33 , 34 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our findings demonstrated that although HDPs, MTA or a combination of both did not cause inhibition of S. mutans growth under planktonic conditions, these materials have the potential of reducing biofilm performed in 24 h and biofilm performed over 7 days biofilms of S. mutans . Our group also recently demonstrated the ability of MTA extracts to reduce biofilm performed in 24 h and S. mutans biofilm performed over 7 days 32 . Besides, previous studies have demonstrated that the antibiofilm capability of IDR1018 is directly related to its concentration 33 , 34 .…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have not shown any antibacterial effect of MTA on S. mutans under planktonic conditions 30 32 . Our findings demonstrated that although HDPs, MTA or a combination of both did not cause inhibition of S. mutans growth under planktonic conditions, these materials have the potential of reducing biofilm performed in 24 h and biofilm performed over 7 days biofilms of S. mutans .…”
Section: Discussionmentioning
confidence: 81%
“…The results of our preliminary studies on the biomaterials indicate a suppressive effect of ZrO 2 enriched MTA cements on the growth of Streptococcus mutans and Streptococcus sanguinis in suspension. Silva et al [ 52 ] showed that MTA repair HA cement significantly inhibited Streptococcus mutans biofilm formation, however, extracts from this biomaterial did not lower bacterial numbers in suspension. The physicochemical properties of biomaterials affect their antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…MTA Repair HP has antimicrobial action against E. faecalis 20 ; however, a more recent study showed that although MTA Repair HP did not inhibit the planktonic growth of S. mutans , it did reduce S. mutans biofilm formation 21 . In the present study, MTA Repair HP was effective against all microorganisms evaluated except P. endodontalis .…”
Section: Discussionmentioning
confidence: 96%